Effects of insular resection on interactions between cardiac interoception and emotion recognition. (April 2021) - Terasawa, Yuri; Motomura, Kazuya; Natsume, Atsushi; Iijima, Kentaro; Chalise, Lushun; Sugiura, Junko; Yamamoto, Hiroyasu; Koyama, Kyohei; Wakabayashi, Toshihiko; Umeda, Satoshi
Abstract: The insular cortex is considered an important region for feeling emotions through interoception. Most studies that report the role of the insula in integrating interoception and emotion have used neuroimaging techniques such as functional magnetic resonance imaging (fMRI); however, there are limited neuropsychological studies. The effects of insular lesions on emotion and interoception have not been suitably investigated. In this study, we examined the role of the insular cortex in cardiac interoception and recognizing emotions from facial expressions by comparing them pre- and post-operatively in patients with glial tumors or brain metastases associated with the insular lobe. Although no significant difference in interoceptive accuracy was observed between the two phases, there were significant associations between the changes in interoceptive accuracy and sensitivity to expressions of anger and happiness. An increased error rate in the heartbeat counting task in the post-operation phase was associated with a decreased accuracy in recognizing anger and happiness. Since most patients had left insula lesions, generalizability of the findings to patients with right lesions is a future subject. To the best of our knowledge, this is the first study to examine the change in interoception and emotion after insular resection in humans. The study results indicate that removal of the insula affects the recognition of emotions such as anger and happiness through interoceptive processing.